TAXATION AND THE NATURAL BUSINESS YEAR. - Preinreich, Gabriel A. D. (The Accounting Review, 1933)
The article focuses on taxation and the business year. The inequality of titration resulting from a difference in accounting periods may be illustrated by a simple although somewhat extreme example adapted from actual practice. Income tax regulations make no specific mention of the matter, but applications for change supported by the plea that the corporate taxpayer wanted to bring its books into agreement with its natural business year have been approved by the Commissioner of the U.S. Internal Revenue Service. The theoretical limits of the natural business year may now be examined from the viewpoint of taxation. The last old closing date will evidently be defined as that point in time, at which the present value of all future income tax payments is a minimum. In order to single out the problem of seasonal fluctuations, it is necessary to disregard changes in profit due to the business cycle, the general long-term trend and the individual trend of the business under consideration. To obtain the amount saved per annum, all that is necessary is to multiply the present value of the total savings by the interest rate.